2003
DOI: 10.1103/physrevd.68.024024
|View full text |Cite|
|
Sign up to set email alerts
|

Higher dimensional black holes and supersymmetry

Abstract: It has recently been shown that the uniqueness theorem for stationary black holes cannot be extended to five dimensions. However, uniqueness is an important assumption of the string theory black hole entropy calculations. This paper partially justifies this assumption by proving two uniqueness theorems for supersymmetric black holes in five dimensions. Some remarks concerning general properties of non-supersymmetric higher dimensional black holes are made. It is conjectured that there exist new families of sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
408
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 202 publications
(420 citation statements)
references
References 48 publications
(73 reference statements)
10
408
1
Order By: Relevance
“…H = H ∩ Σ where Σ is a spacelike slice that intersects H). In the ungauged theory considered in [33] it was shown that these equations can be completely solved when H is compact and the near-horizon geometry can therefore be determined explicitly. This has also been done in the minimal six-dimensional ungauged supergravity [28].…”
Section: General Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…H = H ∩ Σ where Σ is a spacelike slice that intersects H). In the ungauged theory considered in [33] it was shown that these equations can be completely solved when H is compact and the near-horizon geometry can therefore be determined explicitly. This has also been done in the minimal six-dimensional ungauged supergravity [28].…”
Section: General Analysismentioning
confidence: 99%
“…Therefore it is not possible to identify which solutions have horizons just by looking at the solution in the form presented above. We shall instead adopt the approach introduced in [33]. This approach is equally valid for timelike or null solutions.…”
Section: General Analysismentioning
confidence: 99%
See 3 more Smart Citations